Strengthening Children's Character through Homeschooling in Islamic Education - Fatma Izzatun Najwa; Maulin Maulin; Ajahari Ajahari (ANWARUL, 2026)
Children’s character development today faces challenges due to social changes and technological advances that have contributed to the weakening of the values of discipline, responsibility, and religiosity. This study aimed to analyze the role of homeschooling in strengthening children’s character based on the perspective of Islamic Education. This study used a library research method with a descriptive qualitative approach through a review of various relevant literature, including books, journals, and scientific articles. Data were collected through documentation study and analyzed using content analysis techniques. The results showed that homeschooling in Islamic Education plays an important role in shaping children’s character through an integrated family environment. The dominant characters formed include being religious, independent, disciplined, honest, responsible, caring, and courteous. The process of strengthening character takes place through learning flexibility, habituation to worship, parental role modeling, family interaction, and consistent supervision. These findings confirm that homeschooling functions not only as an alternative form of education but also as a strategic means of strengthening children’s character based on Islamic values. The implications of this study indicate that parents have a central role as educators as well as the primary character builders of children within the family environment.